Analisis Karakteristik Peserta Didik dalam Pembelajaran Fisika untuk Pengembangan Buku Digital (e-book) Fisika SMA Berbasis Model Discovery Learning - Putri, Gema Eferko; Festiyed, Festiyed (Universitas Negeri Padang, 2019)
Facing the era of globalization, government then developed the 2013 curriculum. The characteristics of the 2013 curriculum were designed with the aim of creating students who meet 21st century competencies that emphasize the ability to think. To achieve that, all 2013 curriculum suggest discovery learning model. This model can be integrated in e-book teaching materials. This study aims to describe the characteristics of students as e-book users and the results of the analysis will be a reference in the development of e-book Physics High School based on discovery learning models. The method used in this research is a descriptive method with data collection instruments in the form of a student questionnaire consisting of four characteristics of students namely independence of learning, interest, motivation and learning style. From the results of the analysis it can be illustrated that students have a low level of independence, interest and motivation and the most dominant learning style is visual. These results indicate that the development of high school physics e-books based on discovery learning needs to be done by considering the learning style aspects when designing